What drives interbank loans? Evidence from Canada - Narayan Bulusu; Pierre Guérin (Bank of Canada, 2018)
We identify the drivers of unsecured and collateralized loan volumes, rates and haircuts in Canada using the Bayesian model averaging approach to deal with model uncertainty. Our results suggest that the key friction driving behaviour in this market is the collateral reallocation cost faced by borrowers. Borrowers therefore adjust unsecured lending in response to changes in short-term cash needs, and use repos to finance persistent liquidity demand. We also find that lenders set rates and haircuts taking into account counterparty credit risk and collateral market price volatility.
Keywords: C55; E43; G23; 330; Financial markets; Wholesale funding